The rules for conjugating (ayin) letter in three-letters verbs - Al Zahrani, Sarah Hassan (Journal of Humanities & Social Sciences, 2017)
Praise be to Allah, Lord of the Worlds, and peace and blessings be upon the prophets and messengers, Prophet Muhammad and all his family and companions. Then this research is entitled: (The rules for conjugating (ayin) letter in three-letters verbs - an analytical descriptive study), based on the study of some of the grammar, He referred to it in his exclusive and thorough manner, which relates to the eye of the tripartite action. These rules were collected, studied and discussed in the light of linguistics. The verb was defined in the morphological balance, its conditions and movements vary, and the changes of the word and the conditions of the construction change. Hebron was one of the first scholars to refer to it in their writings. The Hebron approach is reflected in its study of these rules. On what he heard about the Arabs and the Pasha and no difference about his health, the two rules Saiban with weighting to listen.
Keywords: grammar; Arabic language; triple verb